BEGINNING OF DAUGAVPILS CHARITY SISTERS’ SCHOOL FOUNDATION (1939−1943) - Fokina, Olga; Millere, Inga; Deklava, Liāna; Circenis, Kristaps (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The Latvian Red Cross organization was founded in 1918 and one of its activities was foundation and maintenance of hospitals in various towns and cities of Latvia. The need for well-prepared charity sisters emerged due to expanding range of medical activities. Consequently, this caused the need to establish sisters’ schools in Latvia. In 1921 charity sisters’ schools were established in Riga and Liepaja, in 1932 the school was established in Jelgava. Later on, in 1939 two more charity sisters’ schools in Riga started their work. However, the demand for charity sisters was growing. The lack of charity sisters was obvious in Daugavpils medical institutions, too. In 1939 the only Latgalian charity sisters’ school was opened in the city to solve that vital problem. That school in Daugavpils worked from 1939 to 1943. During that particular period of time two graduations of educated charity sisters took place. In 1943 the school stopped functioning because of the war situation. This article aims at performing analytical overview of foundation activities of Daugavpils Charity Sisters’ School.